The Sociology of Ritual and Resistance: Constructing Religious Educational Meaning in the Marginal Spaces of Pastoral Care - Teresia Noiman Derung; Bernadeta Sri Jumilah; Rosalia Ina Kii; Andri Fransiskus Gultom (Lembaga Bale Literasi, 2025)
This article examines the sociological reconceptualization of religious education within the marginal spaces of pastoral care through the lens of the dialectic of ritual and resistance. Previous studies on pastoral care have tended to frame ritual either theologically or psychologically, neglecting how structural inequality, class marginality, institutional exclusion, and power asymmetries shape the production of meaning in religious education. Employing a qualitative case study in three urban pastoral communities in Indonesia, this research utilizes participant observation and in-depth interviews with 34 pastoral actors (clergy, lay volunteers, and marginal parishioners). Data analysis was conducted through thematic analysis guided by an abductive logic, moving iteratively between empirical data and the framework of the sociology of ritual. The findings demonstrate that ritual operates as a double-edged mechanism: reproducing hegemonic narratives while simultaneously providing a tactical space for marginal actors to enact subversion through embodied performance, vernacular reinterpretation, and collective improvisation. This dialectic gives rise to what we formulate as